Macs All-in-One For Dummies, 5th Edition - Hutsko, Joe; Boyd, Barbara; Sahlin, Doug; Feiler, Jesse; Boyd, Barbara (Freelance writer) (--For dummies., 2020)
Your all-in-one guide to the wonderful world of your Mac Are you getting the most from your Mac? Given what's possible, it's pretty unlikely. Whether you're just beginning your journey or are already a seasoned traveler, the six information-packed minibooks included in Macs All-in-One for Dummies open up a world of knowledge, from how to set up a recently bought Mac to exploring the coolest new features on your beloved device. Now updated with what you need to know about the newest generation of hardware and software, Macs All-in-One For Dummies is your guide to simply everything: protecting your Mac; backing up and restoring data with Time Machine; managing applications on the Dock, Launchpad, and Desktop; syncing with iCloud, organizing your life with Calendar, Reminders, Notes, and Notifications; presenting with Keynote; crunching with Numbers; getting creative with iMovie and GarageBand-the list goes on! Explore the newest version of MacOS Set up and customize a new Mac with ease Become more efficient, professional, smart, and creative with the latest must-have apps Use Home Sharing to stream content to other computers, iOS devices, and Apple TVs Dive into six books in one place: Mac Basics, Online Communications, Beyond the Basics, Your Mac as a Multimedia Entertainment Center, Taking Care of Business, and Mac Networking Whatever you want from your world of Mac, you'll find it here-as well as a million other incredible things you'll love. Get started on your new Mac journey today!